Optimization and scale up of production of alkaline protease from Conidiobolus coronatus - Laxman, Ryali Seeta; Sonawane, A. P.; More, Shivaji V.; Rao, B. S.; Rele, M. V.; Jogdand, Vitthal V.; Deshpande, V. V.; Rao, M. B. (Process Biochemistry, 2005)
Alkaline protease secreted by Conidiobolus coronatus has been evaluated extensively in tanneries and finds application in pre-tanning operations in leather manufacture. It is important to produce the enzyme in inexpensive and optimized media on large scale for the process to be commercially viable. The present paper describes optimization of fermentation conditions in shake flasks and scale up of production to 100 L in fermentors. The production is complete in 2-3 days comparable to bacterial fermentations. The organism utilized several carbon sources such as starch, sucrose, lactose, glucose and fructose for production. Soyabean meal at an optimum concentration of 2-3% was found to be best inducer. Diammonium hydrogen phosphate, casamino acids and Hi-media peptone gave activities comparable to yeast extract. Preservation and stabilization studies showed that glycerol conferred considerable stabilization at room temperature while ammonium sulphate precipitated enzyme at 0.9 saturation was best with stability up to 2 years even at room temperature. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Alkaline Protease; Conidiobolus; Fermentation; Optimization; scale up

Morphological mutants of gibberella fujikuroi for enhanced production of gibberellic acid - Lale, Geetanjali; Jogdand, Vitthal V.; Gadre, Ramchandra V. (Journal of Applied Microbiology, 2006)
Aims: To examine the production of gibberellic acid by selected morphological mutants of Gibberella fujikuroi in liquid cultures. Methods and Results: Mutants of G. fujikuroi having different morphological characteristics were selected after UV irradiation. The production of gibberellic acid by mutants that had different hyphal lengths was examined in shake flasks in media with different concentrations of nutrients as well as different volumes of the medium. Fed-batch fermenter study was performed to evaluate the mutant Mor-25 for growth and production of gibberellic acid. The broth was analysed by high performance liquid chromatography for fusaric acid, the common mycotoxin produced by strains of Fusarium. A variety of morphological mutants having different mycelial and soluble pigmentation as well as colony morphologies were generated from G. fujikuroi upon exposure to UV radiation. A nonpigmented mutant (Car-1) was selected as intermediate parent and later, mutants Mor-1 and Mor-25 were selected based on their distinct morphology. The colonies on regeneration agar plates were small, compact and dry. In liquid medium, mutant Mor-25 grew in a micro-pelleted form and the mycelium had short, highly branched hyphae, curly at tips with thick, swollen cells. Mutant Mor-25 grew rapidly in a low-cost medium containing defatted groundnut flour, sucrose and salts. In media with higher nutrient concentrations as well as larger volumes, it produced twofold more gibberellic acid than the parent. Fusaric acid, the common mycotoxin, was absent in the fermentation broth of mutant Mor-25. The mutants have been deposited in National Collection of Industrial Microorganisms (NCIM), National Chemical Laboratory, Pune, India under following culture collection numbers (Car-1, NCIM 1323; Mor-1, NCIM 1322; and Mor-25, NCIM 1321). Conclusion: Growth of unpigmented, morphological mutants of G. fujikuroi that led to lower viscosity in fermentation broth resulted in increased production of gibberellic acid. Significance and Impact of Study: The use of morphological mutants that have lower viscosity in liquid cultures for gibberellic acid production is not reported earlier. Similar mutants can be useful for other types of fungal fermentations also.

Production and single step purification of cyclodextrin glycosyltransferase from alkalophilic bacillus firmus by ion exchange chromatography - Savergave, Laman S.; Mule, Santosh S.; Jogdand, Vitthal V.; Nene, Sanjay N.; Gadre, Ramchandra V. (Biochemical Engineering Journal, 2008)
Production and purification of starch digesting cyclodextrin glycosyl transferase (CGTase) from alkalophilic Bacillus firmus was investigated. Fermentation was carried out in 141 bioreactor at 28 degrees C using a medium containing dextrin, yeast extract, peptone, (NH4)H2PO4 and MgSO4.7H(2)O. The extracellular enzyme was concentrated by tangential flow ultrafiltration. The concentrated enzyme was chromatographed using DEAE-sepharose and phenyl sepharose. DEAE-sepharose could be used to purify CGTase in a single step with 23.1 fold purification and 80.6% recovery. The enzyme obtained had homogeneity and the molecular weight was 76 kDa confirmed by SDS-PAGE. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: alkalophilic; Bacillus firmus; CGTase; cyclodextrin; Purification

Simple and efficient enzymatic transglycosylation of stevioside by beta-cyclodextrin glucanotransferase from Bacillus firmus - Jaitak, V.; Kaul, V. Kumar; Bandna; Kumar, N.; Singh, B.; Savergave, L. S.; Jogdand, Vitthal V.; Nene, S. (Biotechnology Letters, 2009)
Stevioside was subjected to 1,4-intermolecular transglycosylation using beta-cyclodextrin glucanotransferase (beta-CGtase) produced from an alkalophilic strain of Bacillus firmus. The reaction was carried out by traditional, ultrasound-assisted and microwave-assisted techniques. Reaction under microwave conditions was faster and was completed in 1 min yielding two 1,4 transglycosylated products, 4'-O-alpha-d-glycosyl stevioside (I) and 4''-O-alpha-d-maltosyl stevioside (II) in 66% and 24%, respectively. The optimum transglycosylation occurred by using stevioside (1.24 mmol), beta-CD (1.76 mmol) and beta-CGtase (2 U/g) under microwave assisted reaction (MAR) in 5 ml sodium phosphate buffer (pH 7) at 50A degrees C and 80 W power. MAR is therefore potentially a useful and economical method for faster transglycosylation of stevioside.
Keywords: beta-cyclodextrin; beta-Cyclodextrin glucanotransferase; Microwave-assisted reaction; Stevia rebaudiana; Stevioside; Transglycosylation

Two-stage fermentation process for enhanced mannitol production using Candida magnoliae mutant R9 - Savergave, Laxman S.; Gadre, Ramchandra V.; Vaidya, Bhalchandra K.; Jogdand, Vitthal V. (Bioprocess and Biosystems Engineering, 2013)
Mutants of Candida magnoliae NCIM 3470 were generated by treatment of ultra-violet radiations, ethyl methyl sulphonate and N-methyl-N'-nitro-N-nitrosoguanidine. Mutants with higher reductase activity were screened by means of 2,3,5-triphenyl tetrazolium chloride agar plate assay. Among the screened mutants, the mutant R9 produced maximum mannitol (i.e. 46 g l(-1)) in liquid fermentation medium containing 250 g l(-1) glucose and hence was selected for further experiments. Preliminary optimization studies were carried out on shake-flask level which increased the mannitol production to 60 g l(-1) in liquid fermentation medium containing 300 g l(-1) glucose. A two-stage fermentation process comprising of growth phase and production phase was employed. During the growth phase, glucose was supplemented and aerobic conditions were maintained. Thereafter, the production phase was initiated by supplementing fructose and switching to anaerobic conditions by discontinuing aeration and decreasing the speed of agitation. The strategy of two-stage fermentation significantly enhanced the production of mannitol up to 240 g l(-1), which is the highest among all fermentative production processes and corresponds to 81 % yield and 4 g l(-1) h(-1) productivity without formation of any by-product.
Keywords: Candida magnoliae; D-Mannitol; Mutagenesis; Strain improvement; Two-stage fermentation